Efficacy and safety of edoxaban in patients with chronic thromboembolic pulmonary hypertension: protocol for a multicentre, randomised, warfarin-controlled, parallel group trial - KABUKI trial - Keiichi Fukuda; Satoshi Yasuda; Hiroyuki Tsutsui; Toyoaki Murohara; Kohtaro Abe; Koichiro Tatsumi; Junji Kishimoto; Yu Taniguchi; Yuichi Tamura; Koji Todaka; Shun Minatsuki; Kazuya Hosokawa; et al. (BMJ Open)
Introduction Chronic thromboembolic pulmonary hypertension (CTEPH) is a complication of prior pulmonary thromboembolism (PE), caused by incomplete clot dissolution after PE. In patients with CTEPH, lifelong anticoagulation is mandatory to prevent recurrence of PE and secondary in situ thrombus formation. Warfarin, a vitamin K antagonist, is commonly used for anticoagulation in CTEPH based on historical experience and evidence. The anticoagulant activity of warfarin is affected by food and drug interactions, requiring regular monitoring of prothrombin time. The lability of anticoagulant effect often results in haemorrhagic and thromboembolic complications. Thus, lifelong warfarin is a handicap in terms of safety and convenience. Currently, the use of direct oral anticoagulants (DOACs) in CTEPH has increased with the advent of four DOACs. The safety of DOACs is superior to warfarin, with less intracranial bleeding in patients with non-valvular atrial fibrillation and venous thromboembolism. Edoxaban, the latest DOAC, also has proven efficacy and safety for those diseases in two large clinical trials; the ENGAGE-AF trial and HOKUSAI-VTE trial. The present trial seeks to evaluate whether edoxaban is non-inferior to warfarin in preventing worsening of CTEPH.Methods and analysis The KABUKI trial (is an investigator-initiated, multicentre, phase 3, randomised, single-blind, parallel-group, warfarin-controlled, non-inferiority trial to evaluate the efficacy and safety of edoxaban versus warfarin (vitamin K Antagonist) in subjects with chronic thromBoembolic pUlmonary hypertension taking warfarin (vitamin K antagonIst) at baseline) is designed to prove the non-inferiority of edoxaban to warfarin in terms of efficacy and safety in patients with CTEPH.Ethics and dissemination This study is approved by the Institutional Review Board of each participating institution. The findings will be published in a peer-reviewed journal, including positive, negative and inconclusive results.Trial registration number NCT04730037.Protocol version This paper was written per the study protocol V.4.0, dated 29 January 2021.